Cyber Community, Cyber Cultures : Arsitektur Sosial Baru Masyarakat Modern - Hendri Prasetyo (Universitas Multimedia Nusantara, 2012)
Cyberspace is a brave new world that cretaes a new cultural form comes from daily life interaction among the user by computer network technology. People creates selves through social interactions and built sense of community – virtual community. Meaning and reality that constructed and shared within the cyberspace turns to cybercultures containing the feelings, attitude, emotional and pattern of behavior – also specific communication behavior. Pattern of pattern behavior existing a set of norms, value that maintaining through continuous interaction and become a social map of meaning. This paper try to capture cyberspace and cybercultures from Gidden’s structurations stand point that view a user as an agent that constructing meaning and subjective reality of cyberspace with their cultural perspective. It’s offering a unique phenomena when people from different culture dealing with cyberspace activity and creating specific cybercultures. Keywords: Cyberspace, Cyber Community